Trophic and Guild in Biological Interactions Control - Brodeur, Jacques; Boivin, Guy.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
This volume explores modern concepts of trophic and guild interactions among natural enemies in natural and agricultural ecosystems - a field that has become a hot topic in ecology and biological control over the past decade. Internationally recognized scientists have combined their expertise and passion to examine how species interactions between biological control agents, such as competition, predation, parasitism, disease infection, mutualism, and omnivory affect arthropod population dynamics and the outcome of biological control. The common approach is the use of ecological theory to better interpret the prevalence, nature and outcome of trophic and guild interactions and, from a more applied perspective, to gain a comprehensive understanding of how and when to use biological control.
The Influence of Intraguild Predation on the Suppression of a Shared Prey Population: An Empirical Reassessment -- Intraguild Predation Usually does not Disrupt Biological Control -- Multiple Predator Interactions and Food-Web Connectance: Implications for Biological Control -- Inter-Guild Influences on Intra-Guild Predation in Plant-Feeding Omnivores -- Trophic and Guild Interactions and the Influence of Multiple Species on Disease -- Intra- and Interspecific Interactions among Parasitoids: Mechanisms, Outcomes and Biological Control -- Indirect Effects, Apparent Competition and Biological Control -- Ant-Hemipteran Mutualisms: Keystone Interactions that Alter Food Web Dynamics and Influence Plant Fitness -- Interspecific Competition among Natural Enemies and Single Versus Multiple Introductions in Biological Control -- Experimental Approaches to Understanding the Relationship Between Predator Biodiversity and Biological Control.
Keywords: LIFE SCIENCES; ECOLOGY; BOTANY; PLANT DISEASES; ZOOLOGY; ENTOMOLOGY; LIFE SCIENCES; ENTOMOLOGY; ECOLOGY; PLANT PATHOLOGY; ZOOLOGY; PLANT SCIENCES